Evaluation of Learning as a Commitment: A Critical Pedagogy Perspective - Borjas, Mónica (Rastros Rostros, 2014)
The main objective of this article is to reflect on evaluation as an inherent part of conceptual educational spaces, based on critical theory. The concept of evaluation is revised, examining aspects of its function and the manner in which it should be carried out. First, the purpose and the role of education is pre- sented, and based on this, the significance of evaluation is revised in relation to what it contributes to recognition of the self. In line with this idea, evaluation can be seen not just as a component, or a tool, or an appendix of education, but as an inherent part of it that is linked to learning; it is present from the moment an individual is conscious of learning, and that he or she is capable. We must therefore speak about evaluation in other terms, abandoning the position that reduces it to its instrumental, technical qualities. Finally, it is shown that education can be transformed through evaluation, which from a criti- cal pedagogy perspective thus becomes a prevailing and active commitment